2012
DOI: 10.2217/nnm.12.98
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cell Cluster Size on Intracellular Nanoparticle-Mediated Hyperthermia: Is It Possible to Treat Microscopic Tumors?

Abstract: Aim To compare the measured surface temperature of variable size ensembles of cells heated by intracellular magnetic fluid hyperthermia with heat diffusion model predictions. Materials & methods Starch-coated Bionized NanoFerrite (Micromod Partikeltechnologie GmbH, Rostock, Germany) iron oxide magnetic nanoparticles were loaded into cultured DU145 prostate cancer cells. Cell pellets of variable size were treated with alternating magnetic fields. The surface temperature of the pellets was measured in situ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 23 publications
(40 reference statements)
2
48
0
Order By: Relevance
“…The particles are supplied as suspension in water. The BNF particles are widely used in hyperthermia studies for cancer treatment [6][7][8] and show interesting properties as contrast agent for magnetic resonance imaging [9]. The FeraSpin R particle system from nanoPET is also an iron oxide multi-core particle system with a median particle size of about 70 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The particles are supplied as suspension in water. The BNF particles are widely used in hyperthermia studies for cancer treatment [6][7][8] and show interesting properties as contrast agent for magnetic resonance imaging [9]. The FeraSpin R particle system from nanoPET is also an iron oxide multi-core particle system with a median particle size of about 70 nm.…”
Section: Methodsmentioning
confidence: 99%
“…12,19 To determine the minimum number of cells required for attaining the target temperatures in the hyperthermia region (T < 42°C), we compared several cell pellets containing were investigated by increasing the T from a starting permissive set point of 37°C. At subhyperthermic temperatures of 37 and 40°C, the required amplitude of the AMF was quite small.…”
Section: Magnetic Hyperthermia (Mht) Using Mnps As Nano-heaters To Imentioning
confidence: 99%
“…In their study, Hedayati et al defined the minimum size of a tumor for efficient hyperthermia with an alternating magnetic field. They determined a minimum tumor volume of 1 mm 3 consisting of cells that had incorporated magnetic nanoparticles to facilitate hyperthermia effects [77] . It is of interest to note that Asin et al found no increase in temperature with the application of an alternating magnetic field in vitro .…”
Section: Types Of Hyperthermiamentioning
confidence: 99%